2021
DOI: 10.3389/fpubh.2021.681319
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Video-Based Educational Interventions on Cervical Cancer, Pap Smear and HPV Vaccines

Abstract: Background: Video-based interventions have the potential to contribute to long-lasting improvements in health-seeking behaviours. Ghana's upsurge rate of information and communication technology usage presents an opportunity to improve the awareness of HPV vaccination and screening rates of cervical cancer among women in Ghana. This research aimed to assess the impact of video-based educational intervention centred on the Health Belief and Transtheoretical Models of behavioural changes in promoting HPV vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 68 publications
(59 reference statements)
3
19
1
6
Order By: Relevance
“…The findings of this study demonstrate a significant overall increase in five (perceived knowledge, individual resilience, perceived trust in authorities, perceived vaccine importance, and feeling protected) examined variables immediately following the educational program, to varying degrees of effect sizes. The findings of this study are in line with previous research involving educational programs in which short videos have been shown to be an effective method for improving knowledge, attitudes, and health behavior ( 20 , 25 27 ). Goodman et al found that video education positively improved health beliefs about vaccination against influenza ( 26 ), while Drokow et al ( 27 ) indicated that video education is influential in improving actual uptake of HPV vaccines ( 27 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings of this study demonstrate a significant overall increase in five (perceived knowledge, individual resilience, perceived trust in authorities, perceived vaccine importance, and feeling protected) examined variables immediately following the educational program, to varying degrees of effect sizes. The findings of this study are in line with previous research involving educational programs in which short videos have been shown to be an effective method for improving knowledge, attitudes, and health behavior ( 20 , 25 27 ). Goodman et al found that video education positively improved health beliefs about vaccination against influenza ( 26 ), while Drokow et al ( 27 ) indicated that video education is influential in improving actual uptake of HPV vaccines ( 27 ).…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study are in line with previous research involving educational programs in which short videos have been shown to be an effective method for improving knowledge, attitudes, and health behavior ( 20 , 25 27 ). Goodman et al found that video education positively improved health beliefs about vaccination against influenza ( 26 ), while Drokow et al ( 27 ) indicated that video education is influential in improving actual uptake of HPV vaccines ( 27 ).…”
Section: Discussionsupporting
confidence: 90%
“…Intervening with educational video significantly affected the increase in the value of intention for cervical cancer screening. This is in line with a previous study that states that the desire for early detection of cervical cancer increased from 35.8% to 94.2% after intervention with a video p-value of 0.001 [30].…”
Section: Differences In the Average Of Knowledge Levels Attitudes And...supporting
confidence: 93%
“…After follow-up of this study, willingness for cervical cancer screening was increased by 46.4% in the intervention group, which is greater than two studies done in Nigeria (1.5 and 1.7%) but less than a study done in Ghana (58.4%) [ 6 , 7 , 32 ]. The proportion of participants who had plan to screen within the next 6 months was also increased by 20.9% in the intervention group, which is greater than a study done in Ghana (13.4%) but less than a study done in North America (72%) [ 16 , 32 ]. This might be the fact that the pre-intervention experience of participants could determine the outcome of intervention; hence, 84.2% of participants in the study from Ghana had knowledge on cervical cancer before intervention.…”
Section: Discussioncontrasting
confidence: 62%